IMPLEMENTATION OF DIGITAL LEADERSHIP OF SCHOOL PRINCIPALS IN INDONESIA: SYSTEMATIC LITERATURE REVIEW - Riski, Aulia; Nurdin, Diding; Hartini, Nani; Prajuri, Mohamad Djodi Hardi (Universitas Negeri Medan, 2023)
Digital leadership is strategic leadership that uses technology, particularly digital assets, to further the company's objectives. As for school principals, digital leadership plays a crucial role in anticipating possible issues and in cultivating highly effective educators who are equipped to tackle the demands of 21st-century skills. This study aims to assess Indonesian school principals' digital leadership capabilities. The study discussed in this paper is a systematic literature review (SLR) related to the role of school principals' digital leadership in raising academic standards published within the previous five years. The Preferred Reporting Items protocol for Systematic Reviews and Meta-Analyses (PRISMA) was employed to analyse articles from the Crossref database using Harzing's Publish or Perish software” 40 journal papers were included in this study. The findings of this study show that a school principal's digital leadership skills favour supporting an efficient learning process, which has implications for the accomplishment of previously defined educational goals. The study's findings also suggest that, in order to raise academic standards and meet more ideal learning goals, digital school leadership abilities must be used in the field of education. In order to enhance the implementation of digital leadership in Indonesian schools, stakeholders in education, such as teachers, administrators, and other authorities, can benefit greatly from the research's findings. Furthermore, this study can be used as a springboard for more investigation into this field, which will help us comprehend how to enhance digital leadership to promote innovative and successful learning in Indonesian classrooms. The research's conclusion is that school administrators in Indonesia need more knowledge, assistance, and training when it comes to digital leadership. Due to the swift changes in the educational landscape brought about by technology, stakeholders need to give top priority to enhancing the digital literacy of staff members and principals. This is because integrating ICT to enhance learning and administration requires them to be digitally literate. Additionally, in order to guarantee that the resources and infrastructure required to support the development of effective digital leadership in Indonesian schools are available, cooperation between educational institutions, the government, and training facilities is crucial. By considering these ramifications, we may improve educational outcomes for upcoming generations and create a system of education that is more adaptable to technological advancements.